STRATEGY TO IMPROVE FUNDING AND LENDING PERFORMANCE IN ACHIEVING THE PERFORMANCE TARGET - Indah Nurul Fitria; Haris Santoso (Nurul Jadid University, 2026)
This study aims to analyze strategies for improving funding and lending performance in achieving performance targets at BMT Ar Rahmah Jaya Mulia Metro Branch. The academic issues discussed include strategies for fund collection, financing distribution, and solutions implemented to overcome the institution's operational challenges. This research employed a qualitative approach using a field research design. Data were collected through observation, interviews, and documentation, and then analyzed descriptively through data reduction, data presentation, and conclusion drawing. The results indicate that the funding strategy was implemented through a pick-up service system, family-based services, and strengthened communication with members. Meanwhile, the lending strategy was carried out through business feasibility surveys, periodic monitoring, and persuasive approaches in handling late payments. The findings are also supported by operational data showing that the Non-Performing Financing (NPF) level reached approximately 15% of the total financing amounting to IDR 65 million in December 2024. This condition indicates the need for stronger risk management and more effective financing evaluation. The solutions implemented include strengthening management, improving human resource capacity, optimizing monitoring systems, and providing financial education to members. These integrated strategies are considered capable of supporting operational stability and improving the achievement of BMT performance targets in a sustainable manner